piRNA-Associated Germline Nuage Formation and Spermatogenesis Require MitoPLD Profusogenic Mitochondrial-Surface Lipid Signaling. - Huang, H.; Gao, Q.; Peng, X.; Choi, S.Y.; Sarma, K.; Ren, H.; Morris, A.J.; Frohman, M.A. (Developmental Cell, 2011)
The mammalian Phospholipase D MitoPLD facilitates mitochondrial fusion by generating the signaling lipid phosphatidic acid (PA). The Drosophila MitoPLD homolog Zucchini (Zuc), a proposed cytoplasmic nuclease, is required for piRNA generation, a critical event in germline development. We show that Zuc localizes to mitochondria and has MitoPLD-like activity. Conversely, MitoPLD(-/-) mice exhibit the meiotic arrest, DNA damage, and male sterility characteristic of mice lacking piRNAs. The primary function of MitoPLD seems to be the generation of mitochondrial-surface PA. This PA in turn recruits the phosphatase Lipin 1, which converts PA to diacylglycerol and promotes mitochondrial fission, suggesting a mechanism for mitochondrial morphology homeostasis. MitoPLD and Lipin 1 have opposing effects on mitochondria length and on intermitochondrial cement (nuage), a structure found between aggregated mitochondria that is implicated in piRNA generation. We propose that mitochondrial-surface PA generated by MitoPLD/Zuc recruits or activates nuage components critical for piRNA production.